Analisis Pelanggaran Hukum Hak Asasi Manusia Dalam Kasus Penganiayaan Mario Dandy Terhadap David Ozora - Dewi, Tiwi Ayu Haresa; Aliffia, Nayla; Hendri, Aisyah Febria; Putri, Dwi Cinta Wiliananda; Az-Zikra, Za’im Sya’ban Syauqi; M, Mulyadi (Media Hukum Indonesia (MHI), 2025)
Human rights are basic rights that every person is born with and cannot be revoked by anyone.  The case of Mario Dandy's severe persecution of David Ozora is a clear example of a violation of the right to life, the right to security, and the right to protection from violence guaranteed by the 1945 Constitution and Law No. 39/1999 on Human Rights.  To investigate the types of human rights violations that occurred and how the perspective of human rights law assesses these violations, this research uses a normative methodology, namely a literature study.  The results show that these acts not only violate national law but also violate international human rights.  The court's verdict against the perpetrators shows the importance of fair law enforcement and the equality of every citizen before the law.